University proceedings. Volga region. Social sciences - A.A. Nerush (Известия высших учебных заведений. Поволжский регион: Общественные науки)
t Background. To ensure the successful use of video games in educational and social projects, it is necessary to take into account the likelihood of conflicts between players during communicative interactions. Digitalization is penetrating various areas of society, including leisure, especially among young people. The question arises about the role of video games in patriotic education, historical education and the formation of values among young people. The state regulates the video game industry, developing the domestic market and controlling content. Regulation of video games is aimed at eliminating destructive content and creating games that reflect real historical images and Russian values. However, video games provide space for communicative interactions between players, which can cause conflicts beyond the control of developers or censors. The purpose of the work is to study the causes and specifics of conflicts that arise in online games among Russian youth, in order to expand the possibilities for the practical use of virtual games. Materials and methods. The study of the causes and specifics of conflicts in online games is based on the materials of the author’s sociological study «Communications, rules and conflicts in mod-ern online games», which included two focus group discussions conducted among users of online games aged 18 to 35 years in 2024 year. Results. The results of an analysis of mate-rials from focus group discussions of gamers in the youth segment of the Russian online game audience are presented. Based on the data from the study, the main causes of conflicts between players in online games, specific factors influencing their occurrence, and strategies for conflict behavior were clarified. Conclusions. It has been established that conflicts in online games arise due to communication problems, differences in skills and emotional reactions of players, and competition. They can also be caused by external factors, such as ethnic or political disagreements. Possible resolution strategies include: confrontation (attacks, creating conditions for defeat) or avoidance (blocking, exclusion from the group), and the involvement of external arbitration. Young players rarely resolve conflicts, except with friends.